Beyond Physical Space: The Human and Cultural Complexities in Marine Protected Area Management - Oracion, Enrique G. (Silliman Journal, 2023)
The development and management of MPAs as protective conservation tools involve multiple stakeholders with varying agenda. Using a case study in Dauin, Negros Oriental, Philippines, this paper explores the human and cultural complexities that underlie the controversies that hound MPAs. The cultural politics enveloping the interaction of multiple stakeholders, specifically between MPA managers and resource users from the fishery and tourism sectors, influences MPA success and sustainability. Thus, as a built environment, an MPA has to be managed not only as a social space but as a physical space as well. This is where an anthropological analysis proves to be important in contributing to the environmental discourse and complementing the works of marine and fishery scientists.